PENGEMBANGAN PERANGKAT PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENUMBUHKAN PERILAKU BERTANGGUNG JAWAB SISWA DI SMP NEGERI KOTA BANJARMASIN - Noor Miyati (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2019)
The objectives of this study are: 1) Describe the learning devices used by teachers in PAI learning at Banjarmasin City Public Middle School, 2) Describe relevant learning devices in PAI learning to foster responsible behavior of students in Banjarmasin City Public Middle School, and 3) Describe effectiveness the use of Islamic Education learning tools in fostering the character of the responsibility of students in the Banjarmasin City Public Middle School. The results showed that: 1) The form of learning devices used by teachers in PAI learning (syllabus, RPP, teaching material, LKPD) refers to the 2013 curriculum with aspects of the syllabus consisting of components of subject identity, school identity, core competencies, basic competencies, subject matter, learning, assessment, allocation and learning resources; RPP consists of components of school identity, subjects, subject matter, time allocation, core competencies, basic competencies and indicators, learning objectives, learning materials, learning methods, learning resources, learning media, learning and assessment steps; Teaching materials consist of components of understanding of honesty, trustworthiness and istiqomah which are directly combined with theorems and examples; The LKPD consists of a short and problem description component. 2) Relevant learning tools developed in PAI learning to foster responsible behavior: the syllabus as a whole has the same components as the previous syllabus, but the assessment on the development syllabus uses cognitive products, processes, skills, spiritual attitudes, social attitudes; The RPP as a whole has the same components as the previous RPP, but the development RPP is made for three meetings, while the initial lesson plan is for one meeting only, besides the development RPP also includes the steps of the learning model; teaching materials produced by development have a more organized concept, with each subject being divided into understanding components, propositions and examples accompanied by images of a combination of animation and real portraits; LKPD as a whole has the same components as the initial LKPD, except that the development LKPD is more complete because it contains work procedures, accompanied by drawings, and is accompanied by an answer key. 3) Learning tools as a result of development consisting of syllabus, learning implementation plan (RPP), teaching materials, and LKPD are more detailed and more practical to be used in the learning process of PAI in State Middle Schools in Banjarmasin City. Besides that students are also easier to understand the material presented which is seen from changes in behavior students become more responsible